New vertebral fractures after vertebroplasty: 2 year results from a randomised controlled trial - Staples, MP (Arch Osteoporos, 2015)
PURPOSE: To assess the effect of vertebroplasty (VP) on the risk of further radiologically apparent vertebral fracture within two years of the procedure. METHODS: We conducted a randomised placebo-controlled trial of VP in people with acute osteoporotic vertebral fracture. Eligible participants were randomly assigned to VP (n=38) or placebo (n=40). Cement volume and leakage were recorded for the VP group. Plain thoracolumbar radiographs were taken at baseline, 12 and 24 months. Two independent radiologists assessed these for new and progressed fractures at the same, adjacent and non-adjacent levels. RESULTS: At 12 and 24 months, radiographs were available for 45 (58%) and 47 (60%) participants respectively. There were no between-group differences for new or progressed fractures: 32 and 40 in the VP group after 12 and 24 months compared with 21 and 33 in the placebo group (hazard ratio (HR) 1.80, 95% confidence interval (CI) 0.82 to 3.94). Similar results were seen when considering only adjacent (HR (95% CI): 2.30 (0.57 to 9.29)), and non-adjacent (HR (95% CI): 1.45 (0.55 to 3.81) levels. In all comparisons there was a consistent trend towards higher risk of any type of fracture in the group undergoing VP. Within the VP group, fracture risk was unrelated to total (HR (95% CI): 0.91 (0.71 to 1.17)) or relative (HR (95% CI): 1.31 (0.15 to 11.48)) cement volume, or cement leakage (HR (95% CI): 1.20 (0.63 to 2.31)). CONCLUSION: For patients undergoing VP our study did not demonstrate significant increases in subsequent fracture risk beyond that experienced by those with vertebral fractures who did not undergo the procedure. However, because of the non-significant numerical increases observed, studies with adequate power are needed to draw definite conclusions about fracture risk.